The Effect of Student Character on Critical Thinking Skills and Mathematics Learning Outcomes of Fisrt Grade Elementary School Students - Erika Safitri; Rintis Rizkia Pangestika; Ageng Triyono (BASICA, 2026)
The study aims to examine the effect of students’ character on critical thinking skills and mathematics learning outcomes among first-grade elementary school students. The study aims to examine the effect of students' character particularly discilpine, responsibility, and independence on critical thinking skills and mathematichs learning outcomes among fisrt-grade elementary school students'. The research employed a quantitative approach using simple linear regression analysis. The sample consisted of 28 students. Character data were collected through a teacher-completed observation questionnaire, while critical thinking skills and mathematics learning outcomes were measured using written tests. Data were analyzed using regression assumption tests and hypothesis tests in SPSS. The results revealed that students’ character did not have a significant effect on critical thingking skills (Sig. =  0.991 > 0.05; R2 = 0.000). Substantively, the R2   value of 0.000 indicates that character variabels did not contribute to explaining the variance in students’ critical thinking skills. However, character had a positive and significant effect on mathematics learning outcomes (β = 0.195; Sig. = 0.010 < 0.05), accounting for 22.8% of the variance in learning outcomes. These findings indicate that character traits such as discipline, responsibility, and independence support academic achievement but do not directly influence critical thingking skills in early-grade students. Practically, teachers are encouraged to consistently integrate character reinforcement into daily mathematics instruction to improve learning outcomes, while simultaneously applying structured problem-based and reasoning-oriented activities to specifically stimulate students’ critical thinking skilss. This study suggests that character education and cognitive skill development should be implemented through complementary instructional strategies at the early elementary level.